2019
DOI: 10.1186/s13071-019-3848-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic variation of the bovine tick-borne pathogen Theileria parva in the Great Lakes region of Central Africa

Abstract: BackgroundTheileria parva causes East Coast fever (ECF), one of the most economically important tick-borne diseases of cattle in sub-Saharan Africa. A live immunisation approach using the infection and treatment method (ITM) provides a strong long-term strain-restricted immunity. However, it typically induces a tick-transmissible carrier state in cattle and may lead to spread of antigenically distinct parasites. Thus, understanding the genetic composition of T. parva is needed prior to the use of the ITM vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
6
10
2
Order By: Relevance
“…This clustering pattern could be as a result of recombination although the most highly probable reason could be due to the presence of mixed infection by different strains in the same animal. In contrast to a recent study [51], our study revealed the presence of three main clusters of cattle derived strains in Rwanda.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This clustering pattern could be as a result of recombination although the most highly probable reason could be due to the presence of mixed infection by different strains in the same animal. In contrast to a recent study [51], our study revealed the presence of three main clusters of cattle derived strains in Rwanda.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a high proportion of dS compared to dN coupled with 3 and 11 negative selection sites on Tp1 and Tp2, respectively and an absence of positive selection sites on both genes was indicative of the presence of purifying selection against change in dN as well as absence of selection pressure possibly attributed to the lack of vaccination programmes against ECF and/or the absence of tick control programmes. This, together with the radiating pattern observed on the MJ network further provides substantial evidence of a freely expanding population of T. parva with slightly similar genotypes to Muguga, Kiambu and Serengeti vaccine isolates in Rwanda, as has been reported in other regions [25,28,29,51,52].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, ITM also has significant drawbacks, including a logistically intensive manufacturing process (reviewed in Di Giulio et al 2009). Also, there have been recently verified concerns that ITM is not always as effective against challenge from buffalo-derived T. parva as it is against cattle-derived parasites , and even cattle-derived T. parva from geographically diverse regions could sometimes break through immunity induced by the Muguga cocktail vaccine (Amzati et al 2019). The African buffalo (Syncerus caffer) is an asymptomatic wildlife carrier of T. parva in the region and is the primary mammalian host (Conrad et al 1987).…”
Section: Introductionmentioning
confidence: 99%